Effects of humic electron mediators on reductive dechlorination of polychlorinated biphenyl by consortia enriched from terrestrial and marine environments - Wang, Qiong; Zhang, Dongdong; Li, Xinkai; Wang, Yi; Wang, Heng; Zhang, Zhichao; Song, Wei; Guo, Peng (Frontiers in Microbiology, 2024)
Humic electron mediators can facilitate the reductive dehalogenation of organohalogenated compounds by accelerating electron transfer. To investigate the effect of humic electron mediators on the microbial anaerobic reductive dechlorination of Polychlorinated biphenyls (PCBs), three types of humic electron mediators, humin (HM), humic acid (HA), and anthraquinone-2,6-disulfonic acid (AQDS, HA analogs), were added to PCB dechlorination cultures enriched from different sources in terrestrial and marine environments (T and M cultures). The results showed that meta-and para-site dechlorination occurred in the M culture, while only meta-site dechlorination occurred in the T culture. The dechlorination process N and the dechlorination process H or H' are presented in both cultures. HM enhanced PCB dechlorination metabolic activity in both cultures mainly by promoting meta-site dechlorination. HA showed a weak promoting effect on the M culture by promoting para-chlorine removal but inhibited the dechlorination metabolism of the terrestrial-origin culture, inhibiting meta-chlorine removal. AQDS showed inhibitory effects on both cultures by inhibiting the microbial removal of meta-chlorine. Highthroughput sequencing and qPCR results suggest that HM is not a carbon source for the potential dechlorinating metabolism of Dehalococcoides but may promote reductive dechlorination by changing the community structure, and AQDS may inhibit anaerobic reductive dechlorination of PCBs by inhibiting the growth of Dehalococcoides. This study provides insights into the mechanism of enhancing PCB microbial dechlorination mediated by humic substances and plays a significant role in extending the application prospects of PCBs bioremediation technology.